How Rapid Urbanisation, Neighbourhood Management Affects Living Conditions. A Survey of Agege Local Government Area, Lagos, Nigeria - Ijasan, K.C.; Ogunro, V. O. (Canadian Center of Science and Education, 2014)
This paper explores the issues around urbanisation, neighbourhood degeneration and its effects on the living condition on the residents of Agege area of Lagos, Nigeria. This paper traces the historical background of the area, examines the meaning of neighbourhood degeneration and explores factors responsible for neighbourhood degeneration. The paper adopts quantitative data collection strategies of investigation, and compares these with past literature on the issue. From the survey of 120 households in the area, the study realized street hooliganism; destitution, bad roads and considerable inequality in the distribution of wealth as the greatest problems in the area. It concluded on the need for holistic approach by government to fast-track housing conditions improvement in the entire areas. Moreover, the redevelopment of the area needs to be community-led participatory planning where all stakeholders harness ideas that can be used to improve the present situation of the area.
Correspondence: K. C. Ijasan, School of Construction Economics and Management, University of the Witwatersrand, Johannesburg, South Africa. E-mail: Kola.ijasan@wits.ac.za
Keywords: Agege LGA; degeneration; Lagos state; neighbourhood management; rapid urbanization